MBL2 gene variants coding for mannose-binding lectin deficiency are associated with increased risk of nephritis in Danish patients with systemic lupus erythematosus. (October 2014) - Tanha, N; Troelsen, L; From Hermansen, M-L; Kjær, L; Faurschou, M; Garred, P; Jacobsen, S
Objectives: Autoimmunity may in part result from deficiencies in the processing of apoptotic debris. As mannose-binding lectin (MBL) is involved in such processes, we hypothesized that the variants in the MBL2 gene resulting in MBL deficiency confer an increased risk of nephritis in systemic lupus erythematosus (SLE). Methods: A total of 171 SLE patients attending a Danish tertiary rheumatology referral center were included. Common variant alleles in exon 1 of the MBL2 gene (R52C, rs5030737; G54D, rs1800450; G57E, rs1800451) were genotyped. The normal allele and variant alleles are termed A and O, respectively. The follow-up period was defined as the time from fulfillment of the ACR 1987 classification criteria for SLE until the occurrence of an event (nephritis, end-stage renal disease (ESRD), or death) or end of follow-up. Cox regression analyses were controlled for gender, age and race. Results: During a median follow-up of 5.7 years, nephritis developed in 94 patients, and ESRD developed in 16 of these patients. Twenty-seven patients died. The distribution of the MBL2 genotypes A/A, A/O and O/O was 58%, 35% and 7.0%, respectively. Compared to the rest, O/O patients had 2.6 times (95% CI: 1.2–5.5) higher risk of developing nephritis, and their risk of death after 10 years was 6.0 times increased (95% CI: 1.0–36). MBL serum levels below 100 ng/ml were associated with a 2.0 (95% CI: 1.2–3.4; p  = 0.007) increased risk of developing nephritis. ESRD and histological class of nephritis were not associated with MBL deficiency. Conclusions: Genetically determined MBL deficiency was associated with development of nephritis in SLE patients, but not with histological class of nephritis or ESRD.